(Oxidation of Vitamin A II. : Factors affecting the Rate of Oxidation of Vitamin A with t-Butil Hydroperoxide) - Slamet Pardijanto, Muhammad (Warta Industri Hasil Pertanian, 1989)
This report deals with studies on factors affecting the rates of autoxidation and hydroperoxide oxidation of vitamin A. It is shown that the latter process is much more rapid than autoxidation and the significance of this facts is assessed in relation to oxidative losses of vitamin A in Fatty foods.